2011
DOI: 10.1002/ibd.21456
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status and response to thiopurines in steroid-dependent inflammatory bowel disease

Abstract: Active smoking does not influence the response to thiopurines in steroid-dependent IBD, but may decrease the likelihood of drug tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
2
8
1
1
Order By: Relevance
“…who demonstrated that surgical risk is only increased in smokers not undergoing immunosuppressive therapy. Domenech et al . similarly observed smoking did not influence stricturing or penetrating disease behaviour when patients were medicated with thiopurines.…”
Section: Discussionsupporting
confidence: 91%
“…who demonstrated that surgical risk is only increased in smokers not undergoing immunosuppressive therapy. Domenech et al . similarly observed smoking did not influence stricturing or penetrating disease behaviour when patients were medicated with thiopurines.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Domènech et al . found that smoking does not influence the development of complicated phenotypes in a population receiving thiopurine treatment . In accordance with these findings, we have recently published a large cross‐sectional study supported by the Spanish working group on Crohn′s and colitis, which found no main differences between current smokers and nonsmokers with respect to disease behaviour and complications; smoking, however, was an independent predictor for need of anti‐TNF therapy …”
Section: Introductionsupporting
confidence: 79%
“…The UC cohort had a much higher incidence of deranged LFTs than the CD cohort and this has not been previously noted. Previous authors have reported that smoking is a risk factor for azathioprine intolerance,13 and although these data were not collected and we cannot comment on this finding, this study indicates that female sex and age 50–70 years are additional further risk factors.…”
Section: Discussioncontrasting
confidence: 68%